2022
DOI: 10.1038/s41598-022-16683-5
|View full text |Cite
|
Sign up to set email alerts
|

Late fetal demise, a risk factor for post-traumatic stress disorder

Abstract: Late-term fetal demise including fetal death in utero, late miscarriage and late termination of pregnancy are relatively frequent occurrences. Post-traumatic stress disorder (PTSD) is a pathology that finds its roots in exposure to a life-threatening event or an event related to death. Exposure to fetal death during a late-term fetal demise is, therefore, a situation at risk of trauma. The objective of this study was to assess the prevalence of PTSD symptoms in the short term among patients faced with late fet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…This result is also supported by the findings of Navidian et al [ 35 ]. A study found that among patients who experienced late fetal death, the prevalence of PTSD ranged from 0.6% to 39% [ 61 ]. Furthermore, evidence suggests that miscarriage can increase the risk of PTSD among pregnant women [ 26 , 30 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…This result is also supported by the findings of Navidian et al [ 35 ]. A study found that among patients who experienced late fetal death, the prevalence of PTSD ranged from 0.6% to 39% [ 61 ]. Furthermore, evidence suggests that miscarriage can increase the risk of PTSD among pregnant women [ 26 , 30 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that mental problems increase with pregnancy loss. [10,14,15,[25][26][27][28] In the literature, it is reported that the PTSD symptom score of women with pregnancy loss is significantly higher than the group without pregnancy loss. [5,7,29] Coleman et al found that PTSD symptoms were found in 52.5% of the sample in their study carried out with women experiencing early pregnancy loss.…”
Section: Discussionmentioning
confidence: 99%
“…[5,6] It is important to examine the reactions of women with a pregnancy loss to posttraumatic stress and anxiety, to identify mental problems in the early period, and to define strategies used to cope with the difficulties in terms of protecting the physical and mental health of the woman and the fetus for subsequent pregnancies. Although there are studies examining posttraumatic stress disorder and mental problems in women with pregnancy loss in the international literature, [7][8][9][10][14][15][16] studies examining this issue are limited in Turkey. [5,17] This study was conducted to identify posttraumatic stress disorder symptoms and related factors in women with early pregnancy loss.…”
Section: Introductionmentioning
confidence: 99%